Performance of diamond tool in machining titanium - Ahmad Nazmi, Mohd Rose (2010)
Titanium and its alloys are attractive materials due to their unique high strength-weight ratio that is maintained at elevated temperatures and their exceptional corrosion resistance. PCD is known for its superior characteristics such as hardness, toughness and wear resistance. In this study, the perfomance of PCD has been investigated. The experiments were carried out on CNC turning centre. The cutting speeds selected in the experiments were 77.5736, 90, 120, 150 and 162.4264 m/min. The depth of cut was kept contstant at 0.5 mm. The feed rates used in the experiments were 0.029289, 0.05, 0.1, 0.15 and 0.170711 mm/rev. Tool wear was measured under OLYMPUS BX51M upright optical microscope with a magnification of 5X. All the data were analyzed by using Anova approach in the STATISTICA. The results have shown that the cutting speeds gave more affect on the tool wears compared to the feed rates. The diamond tool wear curve were also successfully developed in this study and compared with the previous study that used coated carbide as the cutting tool. From the data and visual analysis on the tool, it was shown that PCD has the greater performance over coated carbide.